2015
DOI: 10.5114/pg.2015.52184
|View full text |Cite
|
Sign up to set email alerts
|

Enema versus polyethylene glycol for the management of rectal faecal impaction in children with constipation – a systematic review of randomised controlled trials

Abstract: IntroductionRectal faecal impaction (RFI) from functional constipation is a common problem in children. Maintenance therapy should start after successful disimpaction. However, there is uncertainty with regard to the optimal disimpaction regimen.AimWe systematically evaluated the effect of polyethylene glycol (PEG) compared to enema for treating RFI.Material and methodsThe MEDLINE, EMBASE, and the Cochrane Library, with no language restrictions, were searched up to July 2014 for randomised controlled trials (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“… 14 , 16 , 18 Dietary fibers, traditional medicine, and probiotics are commonly used; however, the clinical evidence supporting their use is not clear. 16 , 19 - 22 Prebiotics and probiotics may be effective at improving clinical symptoms, but data from RCTs are limited. 19 , 21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 , 16 , 18 Dietary fibers, traditional medicine, and probiotics are commonly used; however, the clinical evidence supporting their use is not clear. 16 , 19 - 22 Prebiotics and probiotics may be effective at improving clinical symptoms, but data from RCTs are limited. 19 , 21 …”
Section: Resultsmentioning
confidence: 99%
“…14,16,18 Dietary fibers, traditional medicine, and probiotics are commonly used; however, the clinical evidence supporting their use is not clear. 16,[19][20][21][22] Prebiotics and probiotics may be effective at improving clinical symptoms, but data from RCTs are limited. 19,21 Among the nonpharmacological interventions, sacral neuromodulation provides a suitable option for refractory PFC, but it is not frequently used, and data on its clinical benefits in children are limited.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of enemas on disimpaction has been investigated by a limited number of studies. A systematic review included two studies comparing the effect of oral PEG to enemas (dioctyl sulfosuccinate sodium and milk and molasses) for disimpaction in children aged 1–17 years with FC [ 68 ]. The primary outcome was treatment success, defined as the absence of fecaloma in one study and no need to visit the emergency department in the other study [ 68 ].…”
Section: Enemasmentioning
confidence: 99%
“…Patients treated with PEG were excluded from the study because PEG was not available in Japan during the start of the study. Míngues et al [22] and Dziechciarz et al [23] showed that PEG monotherapy is adequate for disimpaction in children with FC, although it is inferior to enemas [23]. In fact, a procedure similar to enema-free disimpaction has been performed in adults undergoing colonoscopy preparation [24].…”
Section: Online Firstmentioning
confidence: 99%